Organic fertilizers and their efficacy on soil characteristics, growth and yield of cauliflower (Brassica oleraceae var. botrytis) in sandy loam soil of Nepal - Ghimirey, Vivek; Chaurasia, Jay; Dhungana, Roshni; Poudel, Balika (Frontiers in Soil Science, 2025)
BackgroundThe application of organic fertilizers not only stimulates cauliflower growth and development but also helps to attain sustainable improvement of soil health. A field experiment was conducted in Chitwan, Nepal from December to March of 2022 and 2023 to explore the effect of different organic fertilizers on the growth, development, and yield of cauliflower.MethodsThis study also analyzed the changes in soil physicochemical properties on sandy loam soil. The research was taken in a one factorial Randomized Complete Block Design (RCBD) with three replications. MS Excel and R-studio were used to analyze the obtained data.ResultsAfter the research, the plant height (54.24 cm), leaf length (42.33 cm), curd diameter (18.26 cm), curd height (11.03 cm), and yield (41.91 t/ha) were significantly higher when poultry manure was applied at 4.63 t/ha in the soil. Similarly, the application of poultry manure revealed significantly higher organic matter (3.93%), total soil nitrogen (0.28%), and soil available phosphorous (110.04 kg/ha). In addition, soil available potassium (187.77 kg/ha) and soil pH (6.84) were seen significantly higher in goat manure (18.94 t/ha) and obifert (10.36 t/ha) respectively which were statistically similar to poultry manure.ConclusionApplication of organic fertilizers was shown to be beneficial; nevertheless, in the long run, poultry manure (4.63 t/ha) can be recommended for sandy loam soil and similar environmental conditions present at the study site to improve cauliflower performance and overall health of the soil.